Contemporary syrian painting as a means of mass communication - Kosiuk, Oksana M. (NGO International Center of Scientific Research, 2025)
The article proves that in the context of coverage of global geopolitical catastrophes, the problem of unambiguous and clear representation of facts is becoming more and more urgent, since each of the participants in the conflict defends their own views on the causes, consequences and unfolding of events. And the mass media rebroadcast the information conflict, completely disorienting the recipients. It is easy to see by looking at how the media of America, Iran, Britain, France, Israel show the war in Syria: the same event is completely unrecognizable in their situational coverage
Keywords: science; fact; genre; documentary; communication; manipulation; information; image; interpretation